HIV-PDI: A protein-drug interaction resource for structural analyses of HIV drug resistance: 1. Concepts and associated database - Ghemtio, L.; Smail-Tabbone, M.; Djikeng, Appolinaire; Devignes, M.; Keminse, L.; Kelbert, P.; Fokam, J.; Maigret, B.; Ouwe Missi Oukem-Boyer, O. (OMICS Publishing Group, 2011)
Overcoming the problem of resistance to antiretroviral drugs (ARVs) in HIV-infected patients is a major issue in AIDS research today. Advances in genome sequencing have facilitated the identification of a growing number of individual genotypes. Hence, it is now possible to understand HIV drug resistance at the molecular level by considering the three-dimensional (3D) structural interactions between ARVs and the mutated viral proteins of patients. Therefore, identification of the critical interactions lost further to one or several HIV mutations, and consequently the modifications of other molecular factors, could be indicators to propose appropriate ARVs escaping the resistance. This paper introduces the HIV-PDI (Protein-Drug Interactions) resource designed to be a decision making tool to propose alternative ARVs against a particular mutated viral protein, and thus to provide a personalized antiretroviral treatment. The HIV-PDI was conceived to serve as an integrated resource for studying HIV drug resistance at the structural level of the protein-drug interaction, with a special emphasis on the active site of the HIV drug target. As a first step, we focus on the well documented protease and related drugs. The HIV-PDI includes clinical information on patients, resistance to given ARVs treatments, HIV proteins structures and mutations, HIV protein/ARV drugs and their 3D interactions. The HIV-PDI may be queried using multiple combinations of fields including protein, drug and treatment conditions and coupled to visualization/analysis tools of 3D Protein-Drug interactions. The HIV-PDI resource can be used in order to help understand the appearance of resistance and to promote further novel drug and treatment developments based on analyses of 3D pattern of protein-drug interactions. A web-based version of HIV-PDI is available at http://hiv-pdi.loria.fr.